Laser synthesis of germanium tin alloys on virtual germanium - Stefanov, S.; Conde, J. C.; Benedetti, Alessandro; Serra, C.; Werner, J.; Oehme, Michael; Schulze, Jörg; Buca, Dan; Hollaender, B.; Mantl, Siegfried; Chiussi, Stefano (Applied Physics Letters, 2012)
Synthesis of heteroepitaxial germanium tin (GeSn) alloys using excimer laser processing of a thin 4 nm Sn layer on Ge has been demonstrated and studied. Laser induced rapid heating, subsequent melting, and re-solidification processes at extremely high cooling rates have been experimentally achieved and also simulated numerically to optimize the processing parameters. In situ measured sample reflectivity with nanosecond time resolution was used as feedback for the simulations and directly correlated to alloy composition. Detailed characterization of the GeSn alloys after the optimization of the processing conditions indicated substitutional Sn concentration of up to 1 in the Ge matrix. © 2012 American Institute of Physics.
CRIS-Team Scopus Importer:2021-06-29